Parahippocampal area three gray matter is reduced in first‐episode schizophrenia spectrum: Discovery and replication samples. Issue 3 (21st November 2020) - Curtis, Mark T.; Coffman, Brian A.; Salisbury, Dean F.
Abstract: Early course schizophrenia is associated with reduced gray matter. The specific structures affected first and how deficits impact symptoms and cognition remain unresolved. We used the Human Connectome Project multimodal parcellation (HCP‐MMP) to precisely identify cortical areas and investigate thickness abnormalities in discovery and replication samples of first‐episode schizophrenia spectrum individuals (FESz). In the discovery sample, T1w scans were acquired from 31 FESz and 31 matched healthy controls (HC). Thickness was calculated for 360 regions in Freesurfer. In the replication sample, high‐resolution T1w, T2w, and BOLD‐rest scans were acquired from 23 FESz and 32 HC and processed with HCP protocols. Thickness was calculated for regions significant in the discovery sample. After FDR correction ( q < .05), left and right parahippocampal area 3 (PHA3) were significantly thinner in FESz. In the replication sample, bilateral PHA3 were again thinner in FESz ( q < .05). Exploratory correlation analyses revealed left PHA3 was positively associated with hallucinations and right PHA3 was positively associated with processing speed, working memory, and verbal learning. The novel use of the HCP‐MMP in two independent FESz samples revealed thinner bilateral PHA3, suggesting this byway between cortical and limbic processing is a critical site of pathology near the emergence of psychosis. Abstract : The early course schizophrenia is associated with reduced gray matter, but the specific structures affected first and how gray matter deficits impact symptoms and cognition remain unresolved. The novel use of the Human Connectome Project multimodal parcellation in two independent first episode schizophrenia‐spectrum samples revealed thinner bilateral parahippocampal area 3, suggesting this byway between cortical and limbic processing is a critical site of pathology near the emergence of psychosis.